(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
There has come an urgent necessity to reconstruct the university building and dormitory on the basis of detailed planning and researches as well as to plan the landscape architecture specifically dedicated to teachers, employees and students step by step according to the standard of higher education organizations. We aim to implement the project taking accounts of not only designs of university campuses in developed countries but also higher education trends in our own country and the mission of Mongolian State University of Agriculture /MULS. The significance of landscape planning is immense. But there is a lack of green environment, convenience, recreation fields, appropriate design etc. at universities and colleges in Mongolia where students, teachers and employees gather in a large number. Therefore, the rationale behind choosing this subject lies in planning and implementing it properly. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 66-72